The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2022
DOI: 10.3389/fpubh.2022.869218
|View full text |Cite
|
Sign up to set email alerts
|

Smartphone Use Time and Total Screen Time Among Students Aged 10–19 and the Effects on Academic Stress: A Large Longitudinal Cohort Study in Shanghai, China

Abstract: ObjectiveThis study aimed to assess smartphone use time and total screen time among students aged 10–19 in Shanghai, China, and examine their effects on academic stress.MethodsBaseline and follow-up surveys were conducted in December 2017 and December 2018, respectively, using a cohort study design with 1,771 participants. Questionnaire surveys and physical examinations of participants were conducted by trained investigators and professional school physicians, respectively. The self-administered questionnaire … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
6
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 9 publications
(6 citation statements)
references
References 43 publications
0
6
0
Order By: Relevance
“…Therefore, when testing the mediating effects, we controlled for these variables to ensure the accuracy and reliability of the results. [50][51][52] The significance level for this study was set at alpha=0.05.…”
Section: Discussionmentioning
confidence: 99%
“…Therefore, when testing the mediating effects, we controlled for these variables to ensure the accuracy and reliability of the results. [50][51][52] The significance level for this study was set at alpha=0.05.…”
Section: Discussionmentioning
confidence: 99%
“…Moreover, compared with primary and middle school students, high school students had less exercise time, more sedentary time, and worse mental health as a result of the higher requirements for study ( 50 , 51 ), which could weaken the relationship between PSU and BP. So far, the majority of literature only use screen time to explore the association between the use of electronic devices and adolescents' health ( 32 , 52 ). However, increasing researchers argued that researchers should not only focus on screen time when exploring the health impact of the use of electronic devices for adolescents ( 53 , 54 ).…”
Section: Discussionmentioning
confidence: 99%
“…Teachers were enrolled to distribute the questionnaires. The detailed questionnaire design has been mentioned in previous study ( 32 ). All participants were asked to fill out a questionnaire regarding several variables, covering demographic information (e.g., age, sex, grade group), behavioral variables (indoor physical activity time, outdoor physical activity time, sedentary time, and screen time), and physiological characteristics (study pressure and well-being).…”
Section: Methodsmentioning
confidence: 99%
“…The current literature supports links between negative associations of social ST and educational activities. Liu et al (2022) examined the effects of smartphone use in students aged 10-19 in Shanghai, China and found that more than 30% of adolescents used smartphones for social and entertainment purposes. Spending ample time on social media and entertainment took time away from participation in other various activities and, therefore, may have influenced children's interest and preferences in completing self-improvement activities such as doing homework, which is vital for their learning development.…”
Section: Association Between Children's St Use and Their Self-reporte...mentioning
confidence: 99%